THE EFFECTS OF HYPERTENSION STAGES ON N-TERMINAL-PRO BRAIN NATRIURETIC PEPTIDE (NT-PRO-BNP) LEVEL AND LEFT VENTRICULAR EJECTION FRACTION - Sriwiyati, Kati; Nasihun, Taufiqurrachman; Abduh, M. Saugi (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2019)
Introduction: Hypertension is the most common risk factor for heart failure causing an increase in N-Terminal-Pro Brain Natriuretic Peptide (NT-proBNP) level and a decrease in left ventricular ejection fraction (LVEF). Objective: To investigate the effect of hypertension on NT-proBNP level and LVEF in patients with chronic heart failure.Methods: This cross sectional study takes 29 people with hypertension stage-1 (HTD-1) and 27 people with hypertension stage-2 (HTD-2) as sample. The left ventricular ejection fraction and NT-proBNP level obtained from medical records are analyzed using independent t test and Mann Withney test, followed with Spearmen correlation between NT-proBNP level and LVEF.Results: Mann-Whitney test indicates that the mean value of NT-proBNP level of HTD-2 is significantly higher compared to that of HTD-1, p = 0,000. On the contrary, the independent t test shows that LVEF in HTD-2 is lower than that of HDT-1, p = 0.001. The Spearman correlation analysis conducted on the NT-proBNP level and the LVEF results in value of -0.651, p = 0.000. The cut-off-point value of NT-proBNP level is 1511pg/ml (sensitivity 0.82% and specificity 0.80%) and the value of area under the ROC curve > 0.7. The left ventricular ejection fraction has an area under the ROC curve > 0.7 with a cut-off-point value of 39% (sensitivity 0.67% and specificity 0.69%).Conclusion: The NT-proBNP level and the LVEF of HTD-2 are significant higher and lower respectively compared to those of HTD-1. The NT-proBNP level and LVEF also show a strong negative correlation. The cut-off-point value of NT-proBNP level and LVEF can be utilized to compare the stages of hypertension in patients with chronic heart failure.